2021
DOI: 10.1186/s13018-021-02260-5
|View full text |Cite
|
Sign up to set email alerts
|

Secreted frizzled-related protein 5 (SFRP5) protects ATDC5 cells against LPS-induced inflammation and apoptosis via inhibiting Wnt5a/JNK pathway

Abstract: Background Secreted frizzled-related protein 5 (SFRP5) is an endogenous inhibitor of Wnt5a (wingless-type family member 5a), which has been implicated in anti-inflammatory response. In this study, we aimed to investigate whether SFRP5 could protect chondrocytes against LPS-induced inflammation and apoptosis. Methods ATDC5 cells that overexpressed with SFRP5 or not were challenged with LPS to observe the effects of SFRP5 overexpression on LPS-trigge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this study, we showed that TNF-α upregulates the expression of Wnt5a through the MAPK-dependent NF-κB pathway. When Wnt5a is involved in the inflammatory process, it also activates the MAPK pathway (including ERK1/2, P38, JNK) and the NF-κB pathway [10,33]. Both the MAPK and NF-κB pathways are also involved in the upregulation of cytokine and chemokine expression [9,34].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that TNF-α upregulates the expression of Wnt5a through the MAPK-dependent NF-κB pathway. When Wnt5a is involved in the inflammatory process, it also activates the MAPK pathway (including ERK1/2, P38, JNK) and the NF-κB pathway [10,33]. Both the MAPK and NF-κB pathways are also involved in the upregulation of cytokine and chemokine expression [9,34].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al studied the effect of Secreted frizzled-related protein 5 (SFRP5), an endogenous inhibitor of Wnt5a, on the inflammatory response of OA and found that overexpression of SFRP5 reduced the expression of inflammatory factors such as IL-1β, IL-6, TNF-α and ROS. Additionally, they demonstrated that SFRP5 attenuates LPS-induced OA inflammation and chondrocyte apoptosis through the Wnt5a/JNK pathway ( Sun et al, 2021 ).…”
Section: The Role Of Wnt Signaling In Cartilage Degenerationmentioning
confidence: 99%
“…The anti-inflammatory function of SFRP5 is exerted by the neutralization of c-Jun N-terminal kinases (JNK) in the downstream of the Wnt signaling pathway, to repress the production of inflammatory cytokines [162,166] (Figure 4). SFRP5 facilitates adipogenic differentiation and adipocyte expansion [167,168].…”
Section: Biological Actionsmentioning
confidence: 99%